PEMANFAATAN GOOGLE FOR EDUCATION (GAFE) DI SMKN 10 JENEPONTO - Musdar, Izmy Alwiah; Muriati, St. (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2019)
SMK Negeri 10 Jeneponto is a Vocational School located in Sapaloe Tolo Timur Kelurahan, Kelara District, Jeneponto Regency. This school has facilities that support students and teachers to utilize IT in teaching and learning. The facilities are Computer Lab and internet connection. However, after conducting interviews with the principal of SMK Negeri 10 Jeneponto, those facilities are not yet utilized optimally. Therefore, it is proposed to do community service that applying GAFE to maximize those facilities. This Community service has some steps. They are website development, GAFE account creation, socialization of the school website, socialization of the GAFE for teachers and evaluation of community service activities. The results of this community service is the schools can manage the web pages themselves. The teachers stated that it is very necessary to implement GAFE to support learning activities in schools but it is still constrained on internet networks that are less stable and not all students have smartphones to support them using GAFE.